Is Law Possible? - Love, Jeff (Studies in East European thought, 2025)
Ivan Ilyin’s text, On the Essence of Legal Consciousness [O sushchnosti pravosoznania], appears to be a straightforward exposition of law as a project of creating a genuine society, a stable order in which individuals are joined together in a common concern (obshchee delo) that strives toward perfection, a formal model reflecting the traditional Orthodox striving to be at one with God (theōsis) (Il’in 2023).1 Not unlike this striving to be one with God, the structuring of that striving as a perfection of what Ilyin refers to as legal consciousness may well be infinite, raising pointed and obvious questions about law as a system of norms and the grounding of law in a striving that infinitely defers the end it sets for itself while maintaining that end as a guide. [...]the introductory essays, ranging from Paul Robinson’s succinct and elegant preface, to useful discussions of Ilyin’s life and the origins and nature of the legal treatise and its principal concept, legal consciousness (pravosoznanie), provide excellent introductions to the treatise that orient one to its main points effectively and as a proleptic response to the apparently diffuse character of Ilyin’s writing. Ilyin prefers to clarify suggestively: A consistent, analytical disclosure of ideas of a living spiritual being, of spiritual freedom, of spiritual self-activity, of spiritual dignity and equality can establish an entire system of natural subjective rights and duties, forming together what it is appropriate to call natural law, the common formulation of which permits one to speak of natural law in an objective sense. If natural law is the articulation of a hitherto unconscious or intuitive truth, how can we find a substantive standard by which to judge the accuracy of the articulation—how can we know the difference between positive law and natural law?